Relationship between learning examination stress and safety performance among employees in Chinese railway workplace: the moderating role of occupational calling - Sun, Jiahui; Ma, Jinfei; Yang, Lu; Yang, Shuwen; Shen, Zhuo; Zhou, Zhiheng; Shi, Lei (Scientific reports, 2025)
Workplace learning is prevalent in corporate environments. However, unreasonable workplace learning can induce stress among employees. Based on the Job Demands-Resources (JD-R) theory, this study aims to explore whether the resulting stress constitutes a hindrance job demand when learning tasks in the workplace are overly burdensome and examinations are excessively difficult and whether this stress compromises employees’ sleep quality and induces shortcut motivation, thereby reducing safety performance. Data from 723 employees was collected, confirm that both sleep quality and shortcut motivation mediate the impact of workplace learning examination stress on safety performance. The study also introduces occupational calling as a personal resource that mitigates the negative effects of workplace learning examination stress. Our research enriches our understanding of the impact of workplace learning and occupational calling on safety performance, with significant implications for employee safety and health.